Late Cenozoic Stress State in Gulf of Güllük and Surroundings, SW Anatolia - Erdem Gündoğdu; Suha Ozden; Alper Demirci (Journal of Advanced Research in Natural and Applied Sciences)
This study was performed with the aim of revealing the Late Cenozoic stress state of the Gulf of Güllük and close surroundings. In this study, the tectonic regime and stress states from the Pliocene to the present day were determined. Mesoscopic fault plane data were collected from outcrops at 19 different stations in the region between the Gulf of Güllük and Milas. Additionally, focal mechanism inverse solutions were calculated for 12 earthquakes larger than M:3.0 occurring from 2004 to 2015 to reveal the current tectonic regime. According to kinematic analysis results from fault assemblages and focal mechanism solutions for earthquakes, two tectonic regimes affected the region before the Pliocene and at present. In the first tectonic regime, strike-slip faulting developed under a NW-SE oriented compressional regime. There was an R ratio of 0.426 between the principal stress axes and this shows faulting had transtensional character. The region converted to a NE-SW oriented extensional regime dominated by normal faulting in the Quaternary. This currently effective extensional regime was understood from focal mechanism solutions of earthquakes developing in the region. The reason for this regime being effective is the rapid pull by the African plate on the Anatolian plate, which rides above the African plate, and horizontal extension in the Anatolian plate.